Updating the national list of marine alien species in Morocco - MGHILI, BILAL; LAMINE, IMANE; RAMI LAAMRAOUI, MOHAMED; AKSISSOU, MUSTAPHA; GALANIDI, MARIKA (Mediterranean Marine Science, 2024)
This study provides an updated list of alien marine species that have been introduced to Morocco by analyzing both previous data and new findings. A total of 46 marine alien and 15 cryptogenic and crypto-expanding species were recorded in Moroccan waters. Alien species are more abundant in the Mediterranean (35 species) than in the Atlantic (16 species) waters. The number of records of introductions increased in recent years in Moroccan waters. Macrophyta ranked first in terms of the number of species (19 species), followed by Mollusca (8 species), Crustacea (7 species), Cnidaria (5 species), Pisces (3 species), and Tunicata (2 species), while Nematoda and Annelida each contain only one species. The finding of Phyllorhiza punctata, a new species recorded for the first time in the Moroccan Mediterranean waters, is described. The Moroccan Mediterranean harbors more established species (77%) than the Atlantic (69%), contrary to casual records (25% in the Atlantic and 20% in the Mediterranean). Within Moroccan waters, 12 species have been identified as either invasive or potentially invasive: Rugulopteryx okamurae, Sargassum muticum, Asparagopsis armata, Asparagopsis taxiformis, Caulerpa cylindracea, Codium fragile, Agarophyton vermiculophyllum, Artemia monica, Callinectes sapidus, Caprella scaura, Microcosmus squamiger, and Branchiomma luctuosum. The Transport- Stowaway pathway accounted for 23 and seven records in the Mediterranean and Atlantic, respectively. In the Mediterranean, the second most frequent pathway was Transport-Contaminant (6 species), while in the Atlantic was Escape (4 species). This list serves as a starting point for management measures and for selecting invasive alien species to assess their impact.